Trunk motion and anterior cruciate ligament injuries: a narrative review of injury videos and controlled jump-landing and cutting tasks - Song, Y.; Li, L.; Hughes, G.; Dai, B. (Sports Biomechanics, 2023)
The aims of this narrative review were to summarise trunk motion and external trunk perturbation observed in anterior cruciate ligament (ACL) injury videos and to review the association between trunk motion and ACL loading variables in controlled jump-landing and cutting tasks in non-injured populations. Video analyses have shown limited trunk flexion and increased trunk lateral bending towards the injured leg are associated with increased risk of ACL injuries, while trunk axial rotation away from the injured leg is more frequent than rotation towards the injured leg. Contact with the trunk before and at the time of the injury is common and might increase the risk of ACL injury. Controlled jump-landing and cutting studies have shown that limited trunk flexion and increased trunk lateral bending are associated with increased ACL loading. However, the findings of trunk axial rotation are not consistent with most video analyses. Mid-flight external trunk perturbation could increase ACL loading variables for one leg and is consistent with the videos of trunk-contact ACL injuries. These findings may help understand the role of trunk motion on primary ACL injury mechanisms and improve ACL injury screening tasks and ACL injury prevention strategies with the consideration of trunk motion.